(untitled) (Biodiversitas Journal of Biological Diversity, 2013)
El-Nagerabi SAF, Elshafie AE, AlKhanjari SS. 2014. Endophytic fungi associated with endogenous Boswellia sacra. Biodiversitas 15: 24-30. Endophytic fungi associated with leaves and stem tissues of Boswellia sacra growing in Dhofar Mountains of Oman were investigated from May 2008 through October 2011. The biological diversity, tissue-preference and seasonal variations of fungi were evaluated. Forty-three species and 3 varieties of fungi were recovered as new records from this plant. Of these isolates, 35 species are new reports to the mycoflora of Oman, whereas 12 species were added to the list of fungal flora of the Arabian Peninsula. The genus Alternaria (12 species) is the most prevalent genus recovered from 12.5-83.3% of the screened leaves and stem samples, followed by Aspergillus (5 species, 3 varieties, 6.9-86.1%), Mycelia sterilia (76.4%), Rhizopus stolonifer (62.5%), Drechslera (3 species, 40.3- 54.2%), Cladosporium (3 species, 20.8-52.8%), Curvularia lunata (38.8%), Chaetomium (2 species, 15.3-26.3%), Penicillium spp. (9.8- 27.8%), Fusarium (9 species, 6.9-27.8%), Ulocladium consortiale (27.8%), Mucor hiemalis (19.5%), and the remaining species (Scytalidium thermophilum, Phoma solani, Taeniolella exilis, and Botryodiplodia theobromae) exhibited very low levels of incidence (4.2-11.1%). Endophytic colonization of the leaf tissues was greater (43 species, 3 varieties) comparable to stem tissues (25 species). This indicates heterogeneity and tissue-preference, with no evidence of seasonal variation. Therefore, the isolation of many fungal species and sterile mycelia supports the biodiversity of the endophytic fungi invading B. sacra and the high possibility of isolating more fungal species using advanced molecular techniques